2018
DOI: 10.1186/s12879-018-3240-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal, and spatiotemporal analysis of mumps in Guangxi Province, China, 2005–2016

Abstract: BackgroundThe resurgence of mumps around the world occurs frequently in recent years. As the country with the largest number of cases in the world, the status of mumps epidemics in China is not yet clear. This study, taking the relatively serious epidemic province of Guangxi as the example, aimed to examine the spatiotemporal pattern and epidemiological characteristics of mumps, and provide a scientific basis for the effective control of this disease and formulation of related health policies.MethodsGeographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 46 publications
(35 reference statements)
6
27
1
Order By: Relevance
“…A time series study conducted in Fujian (Hu et al 2018) showed that various meteorological factors, including temperature, relative humidity, air pressure, rainfall, wind speed, and sunshine duration, affect the incidence of mumps, for example, low temperatures and wind velocity were found to increase the risk of mumps. This view is consistent with a study in Guangxi (Yu et al 2018a, b). However, a finding obtained in Guangzhou (Yang et al 2014b) showed that low temperature and wind velocity are protective factors for mumps.…”
Section: Responsible Editor: Gerhard Lammelsupporting
confidence: 92%
See 2 more Smart Citations
“…A time series study conducted in Fujian (Hu et al 2018) showed that various meteorological factors, including temperature, relative humidity, air pressure, rainfall, wind speed, and sunshine duration, affect the incidence of mumps, for example, low temperatures and wind velocity were found to increase the risk of mumps. This view is consistent with a study in Guangxi (Yu et al 2018a, b). However, a finding obtained in Guangzhou (Yang et al 2014b) showed that low temperature and wind velocity are protective factors for mumps.…”
Section: Responsible Editor: Gerhard Lammelsupporting
confidence: 92%
“…Recent studies have shown that meteorological factors may influence mumps incidence (Hu et al 2018;Yang et al 2014b;Yu et al 2018a, b). In the USA (Patel et al 2017), South Korea (Choe et al 2017) and Netherlands (Sane et al 2014), mumps showed a seasonal variation and peaked during spring.…”
Section: Responsible Editor: Gerhard Lammelmentioning
confidence: 99%
See 1 more Smart Citation
“…A spatiotemporal analysis of varicella in Valencia, Spain from 2008 to 2012 identi ed spatiotemporal clusters where the population was economically disadvantaged or perhaps less educated and less aware of vaccination schedules [5]. In spatio-temporal analysis of measles [6] and mumps [7] in China, high-risk clusters were mainly distributed in the urban-rural transition zones or semi-urban areas because, with parents migrating to urban areas for employment opportunities, children were left in impoverished and remote area from vaccination clinics and become susceptible to disease.…”
Section: Discussionmentioning
confidence: 99%
“…With the said database, spatial distribution of the species where identified per region, which led them identify loss of biodiversity and imbalances in the environment (König et al, 2019). Moreover, Yu et al (2018) established that visualizations is important means of communicating and representing massive data sets. Spatiotemporal visualization sometimes in a form of shapefile can be widely used as an instrument to depict results for decision-making processes.…”
Section: Spatiotemporal Visualizationmentioning
confidence: 99%